Strategic Management Accounting Techniques Usage, Strategic Choices, and Performance of Financial Institutions in Nigeria - J.O, Odia (Journal of Asian Business Strategy, 2019)
The paper examined the impact of strategic management accounting (SMA) techniques’ usage and strategic choices on the performance of financial institutions in Nigeria. Based on the administration of questionnaire to 156 top management employees of 13 deposit money banks in Benin metropolis, Edo State the paper examined whether SMA dimensions (17 SMA techniques usage and the participation of accountants in strategic decision making) and strategic choices (strategic pattern, emergent strategy and market orientation) affect the performance of deposit money banks. The findings from the multiple regression analysis showed that whereas SMA techniques usage had a significantly negative impact on corporate financial performance, accountant participation in strategic decision making, strategy pattern, deliberate/ emergent strategy and market orientation had a significantly positive impact on the performance of the banks.Therefore, the paper recommended that management of financial organizations should improve their usage of SMA techniques which is presently low, involve accountants in the strategic decision making process and employ more emergent and market oriented strategies in order to improve their performance.